Implikasi Teori Jean Piaget dalam Pembelajaran Matematika Kelas IV Madrasah Ibtidaiyah Ma’had Islami Purbayan Kotagede - Kurniawan Andika Putra; Eka Parwani; Nur Rohmi; M. Rofi Fauzi (IIQ An Nur Yogyakarta, 2023)
The purpose of this research was to find out the process of learning Mathematics for class IV MI Ma'had Islami from the perspective of Jean Piaget's theory. This research used qualitative methods, data collection was done by means of observation, interviews, and documentation. The results obtained were that the learning of Mathematics in this school entered the concrete operational stage of the child. At this concrete operational stage, students began to think logically about concrete events and clarify objects into different forms. Learning Mathematics for class IV MI Ma'had Islami Kotagede used memorizing and writing methods. If only using the memorization method, students were less able to fully understand the material delivered by the teacher. For this reason, in learning Mathematics in class, students were given the freedom to choose what method they like in learning to facilitate understanding of the material presented by the teacher.